Discretization of urban areas using POI-based tesselation - Tobias Hagen; Jonas Hamann; Siavash Saki (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2022)
Urban area tessellation is a crucial aspect in many spatial analyses. While regular tessellation methods, like square-grid or hexagon-grid, are suitable for addressing pure geometry problems, they cannot take the unique characteristics of different subareas into account. Irregular tessellation methods allow the border between the subareas to be defined more realistically based on the urban features like road network or POI data. This paper studies and compares five different tessellation methods: Squares, hexagons, adaptive squares, Voronoi diagrams, and city blocks. We explain how (open-source) POI data can be integrated into the tessellation process to build what we call 'Local Geographic Units' (POI-based tiles). These units are flexible and adaptable to the structure of the studied area and underlying data and could improve the performance of further analyses. The results of the various tessellation methods are demonstrated for the city of Frankfurt am Main in Germany. A simple clustering of Local Geographic Units for the studied city indicates that city blocks perform better than the other methods in the city segmentation in terms of reflecting the structure of this city. – – Die Tessellierungen urbaner Gebiete ist ein entscheidender Aspekt bei räumlichen Analysen. Regelmäßige Tessellierungen, wie die Unterteilung in Quadrate oder Hexagons, eignen sich zwar für Probleme rein geometrischer Natur, berücksichtigen aber die Charakteristika der enthaltenen kleineren geographischen Einheiten nicht. Unregelmäßige Tessellierungen ermöglichen eine realitätsnahe Unterteilung basierend auf städtischen Merkmalen, wie dem Straßennetz oder POI-Daten. In diesem Beitrag werden fünf verschiedene Tessellierungsmethoden vorgestellt und verglichen: Quadrate, Hexagons, adaptive Quadrate, Voronoi-Diagramme und City-Blocks. Die Integration von (Open-Source) POI-Daten in den Tessellierungsprozess führt zu sogenannten 'Lokalen Geographischen Einheiten'. Diese POI-basierten Einheiten sind flexibel und passen sich sowohl der Struktur des zu untersuchenden Gebiets, als auch der zugrundeliegenden Daten an und erlaube dadurch darauf aufbauende, detailliertere Analysen. Alle vorgestellten Tessellierungsmethoden werden an dem Beispiel Frankfurt am Main durchgeführt und präsentiert. Ein einfaches 'Clustering' der Lokalen Geographischen Einheiten zeigt, dass City-Blocks die Struktur der Stadt besser abbilden können, als die anderen vorgestellten Methoden.
Keywords: 330; urban analysis; tessellation; spatial tessellation; urban studies